Results from a peer-based digital systems navigation intervention to increase HIV prevention and care behaviors of young trans women in Rio de Janeiro, Brazil - Erin C. Wilson; Emilia M. Jalil; Cristina M. Jalil; Cristiane R. V. Castro; Ana Luiza N. Ferreira; Nilo F. Martinez; Nilo F. Martinez; Isabele Moura; Cleo Oliveira; Daniel Bezerra; Eduardo Carvalheira Netto; Laylla Monteiro; et al. (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background This study aimed to determine the efficacy of an evidence-based peer and mHealth delivered systems navigation intervention for increasing human immunodeficiency virus (HIV) testing, pre-exposure prophylaxis (PrEP) and HIV care behaviors among young trans women. # Methods The "Brilhar e Transcender" (BeT) pilot study was conducted between 19 September 2019 and 26 November 2020 in a trans-affirming public health clinic in Rio de Janeiro, Brazil. Participants were recruited using convenience sampling through outreach and referral. Twenty-seven were screened for inclusion and 18 participants completed the study and were included in this analysis. Participants were recruited through community outreach. All participants identified as trans women, were aged 18-24 years old, lived in Rio de Janeiro, Brazil, and were not on PrEP or not engaged in HIV care. Over the course of three months, participants developed a systems navigation plan and were engaged in three peer-navigator sessions, asynchronous digital interactions in between sessions, and received automated information they could use to address services access barriers. We measured HIV testing, PrEP use and HIV care outcomes. HIV care engagement included linkage to care, visit attendance, antiretroviral therapy use, and/or undetectable viral load for those living with HIV. # Results All young trans women without HIV (n=13) were regularly tested for HIV and engaged in PrEP by the end of the intervention. All participants living with HIV (n=5) were engaged in HIV care, but one participant had a detectable viral load post intervention. # Conclusions The BeT intervention demonstrated preliminary efficacy for improving HIV prevention and care behaviors among young trans women in a low- and middle-income country (LMIC) setting. A trial is planned for implementation to establish efficacy with a large sample of young trans women and a comparator group.